CRISPR-Cas12: A Versatile Tool for Genome Editing and Beyond - Xu, Minghuang; Yuan, Fuwen (Serican Journal of Medicine, 2025)
CRISPR-Cas systems are emerging gene editing toolkits that have been used for the manipulation of DNA and RNA, among which CRISPR-Cas12 demonstrates superior properties in terms of target DNA engineering in vivo compared to CRISPR-Cas9 as well as nucleic acid detection compared to CRISPR-Cas13. A comprehensive understanding of the mechanisms and emerging applications of CRISPR-Cas12-based technologies is critical for maximizing their benefits across various fields, including basic science, medicine, and food safety. In this study, we review the molecular features of both natural and engineered CRISPR-Cas12 compared to CRISPR-Cas9 and CRISPR-Cas13, and we provide an overview of established CRISPR-Cas12-based genome editing and diagnostic platforms. Furthermore, we discuss the advantages, challenges, and prospects for future directions of CRISPR-Cas12 in gene editing and nucleic acid detection.